1990
DOI: 10.1111/j.1365-3059.1990.tb02530.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of double‐stranded RNA with whitefly‐mediated silvering in squash

Abstract: A disorder of unknown aetiology appearing as silvering on squash (Cucurbita pepo) leaves has become prevalent in south Florida. Typical symptoms, observed after 2 weeks of exposure to adults of Bemisia tabaci, the sweet potato whitefly (SPWF) include vein clearing followed by silvering of whole leaves. Fruits from affected plants are blanched or streaked longitudinally. The silverleaf syndrome was not mechanically transmissible when crude extracts of symptomatic leaves were used as inoculum. Two sizes of doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The other was termed the B biotype, or the poinsettia strain. The B biotype is more fecund than the A, produces greater amounts of honeydew, has a broader host plant range, exhibits significantly higher levels of insecticide resistance, induces several different phytotoxic disorders in certain plant hosts (Anthony et al, 1995;Bethke et al, 1991;Bharathan et al, 1990;Byrne and Miller, 1990;Cohen et aL, 1992;Brown, 1991, 1993;Liu et aL, 1992), and has recently been proposed as a new species, Bemisia argentifolii (Bellows et aL, 1994;Perring et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The other was termed the B biotype, or the poinsettia strain. The B biotype is more fecund than the A, produces greater amounts of honeydew, has a broader host plant range, exhibits significantly higher levels of insecticide resistance, induces several different phytotoxic disorders in certain plant hosts (Anthony et al, 1995;Bethke et al, 1991;Bharathan et al, 1990;Byrne and Miller, 1990;Cohen et aL, 1992;Brown, 1991, 1993;Liu et aL, 1992), and has recently been proposed as a new species, Bemisia argentifolii (Bellows et aL, 1994;Perring et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…observ.). In Florida, SSL has been associated with feeding by B. tabaci (Maynard & Cantliffe, 1989;Yokomi et al, 1990) and the presence of two double-stranded RNAs (Bharathan et al, 1990). However, the etiology of this disorder is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Following the association of SPW with SSL, two divergent hypotheses were advanced to explain this disorder. Bharathan et al (1990) reported two double-stranded RNAs (dsRNA; 4.6 and 4.2 kilobase pairs, Kb) in leaf extracts from symptomatic plants and implicated this foreign nucleic acid as the causal agent of whiteflyinduced SSL. Yokomi et al (1990) also discovered dsRNA (4.4 and 4.0 x 106 mol wt), but this nucleic acid was only found in the SPW; dsRNA was not found in symptomatic leaves.…”
Section: Introductionmentioning
confidence: 99%